The new world of UN peace operations learning to build peace? - Benner, Thorsten, 1973-; Mergenthaler, Stephan; Rotmann, Philipp (Oxford : Oxford University Press, 2011)
Millions depend on UN peace operations as the main bulwark between state collapse and hopes for peace. 'The New World of UN Peace Operations' takes a critical look at the apparatus tasked to protect civilians in zones of conflict. This is an indispensable resource for those interested in the evolution of modern peace.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United Nations; Peace-building.; Peace-building -- Case studies